EXPERIENCES OF PEOPLE LIVING WITH HIV IN OBTAINING HEALTH INFORMATION : A PHENOMENOLOGICAL STUDY - Nadia Rahmawati; Ikbal Fradianto; R.A Gabby Novikadarti Rahmah (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
People living with HIV (PLHIV) face a complex adaptation process after receiving an HIV diagnosis, particularly in understanding the disease and initiating antiretroviral therapy (ART). Health information plays a critical role in shaping self-acceptance, decision-making, and treatment adherence. This study aimed to explore the experiences of PLHIV in obtaining and interpreting health information. This study employed a descriptive qualitative design with a phenomenological approach. Twelve participants were purposively selected and were active members of a peer support group at Yayasan Pontianak Plus. Data were collected through semi-structured in-depth interviews and observations. Data analysis was conducted using the Colaizzi method. The findings revealed that PLHIV obtain health information from various sources, including non-governmental organizations, peer communities, religious communities, books, social media, and healthcare professionals. Non-governmental organizations and peer communities emerged as the most dominant and meaningful sources because they provide both health education and emotional support. Healthcare professionals were also considered trusted sources of information, particularly regarding antiretroviral therapy. However, differences in participants’ experiences with the initial side effects of ART influenced how they interpreted the information they received. In conclusion, the experience of obtaining health information among PLHIV is multidimensional and shaped by interactions with multiple information sources. Collaborative and patient-centered educational approaches are needed to support treatment adherence and improve the quality of life of PLHIV.